INCREASING COMMUNITY AWARENESS IN JELADRI VILLAGE THROUGH SUPPLEMENTARY FEEDING TO PREVENT STUNTING: AN EFFECTIVE AND SUSTAINABLE APPROACH - Mukhammad Alfani; ’Aisy, Nabilah Rahadatul; Rahmadhani, Novia Alif; Aqillasalsabila, Sufi; Lusiana, Nova (HEARTY, 2024)
Stunting is a serious problem in Indonesia that has a direct impact on growth and development in children. This study focuses on evaluating the effectiveness of the Supplementary Feeding Program (PMT) in Jeladri Village to prevent stunting in children under five. It involves the implementation of the PMT, which provides a nutrient-rich supplementary menu, as well as intensive socialization activities to the village community. The results showed that PMT can have a significant positive impact on improving the nutritional status of children in Jeladri Village. The PMT menu is specially selected and designed to provide nutrition that contains essential nutrients needed for optimal growth in children under five. Nonetheless, the study also identified several obstacles, such as a lack of community understanding and participation in the program. While there has been an increase in awareness of the importance of nutrition for children, further efforts are needed to improve the level of understanding and active community involvement in the PMT program. This is important to significantly reduce stunting rates in the future. In this context, the research recommendations suggest the need to improve national nutrition policies that are more integrated and effective. In addition, a comprehensive and sustainable approach is needed in the implementation of stunting prevention programs across Indonesia. This includes not only nutrition education and access to PMT, but also health system strengthening and support from various parties including local governments.